Developing a Gamified Digital Learning Media to Cultivate Singing Skills for Junior High School Students - Wulandari; Sutimin, Leo Agung; Santosa, Eka Budhi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Digital learning media based on gamification is rarely found in singing education, yet the impact of utilizing such learning tools cannot be underestimated. Therefore, this study aimed to develop a gamified digital learning media product for cultural arts education in junior high schools. The research adopts a Research and Development (R&D) approach using the ADDIE model, focusing on the development and validation process of gamified digital learning media suitable for educational purposes. The research subjects consist of media experts, content experts, and cultural arts teachers from State Junior High School 3 Grogol, Sukoharjo. Data collection techniques involve a media validation questionnaire, which is then analyzed using percentages and described to provide an overview of the suitability level of this gamified media. The research results indicate that the average validation results obtained from media experts I and II are 86%, while the average results from content experts I and II are also 86%. After being validated by the cultural arts teachers, the gamified media received an average total score of 87% from three teachers, all falling under the 'very good' qualification. Therefore, based on the assessments of media experts, content experts, and teachers, it is concluded that the gamified digital learning media product is categorized as 'suitable' for use as an alternative cultural arts learning media in State Junior High School 3 Grogol. The existence of this appropriate media undoubtedly stands as an innovative learning tool, incorporating gaming elements to enrich the process of singing skills.